A hospital-based study of stigmatisation and well-being of relative of mentallv-ill in Ogun State, Nigeria (2022)
The study was a hospital-based one that investigated stigmatisation and well-being of relatives of the mentally-ill in Ogun State It adopted a correlational research design to study 252 relative of mentally-ill-using purposive sampling technique. Self-administered, structured questionnaire and in-depth interview, guides served as instrument for data collection respectively. The data obtained were analysed at univariate and bivariate levels with the aid of statistical package for social science. The findings revealed a weak negative correlation [r(250)=-083,p>0.05] between stigmatisation and self-acceptance among relatives of mentally-ill. A weak negative correlation was also found [r(250)= -167, p<0.05] to exist between stigmatisation and personal growth level of relatives of mentally-ill. Moreover, a weak positive correlation but not significant was found [r(250)=081,p>0.05] between burden of care and care of mentally-ill. However, the contrast was the case with the qualitative finding, it was concluded that stigmatisation has many negative consequences on persons having mental illness including their relatives` well-being in terms of self-acceptance, personal growth and burden of care of mentally-ill